Impact Of Covid 19 on A Cohort of Hemodialysis Patients -A Nested Case Control Study in A Tertiary Care Hospital; Northern Pakistan - Zaid, Farhan; Khan, Malik Nadeem Azam; Aslam, Aakash; Tanveer, Ahsan; Fahad Javed Awan; Butt, Amna (Infectious Diseases Journal of Pakistan, 2024)
Background: The outbreak of the highly contagious coronavirus has significantly threatened human health, particularly for individuals with underlying diseases. Despite this, the effects of the epidemic on hemodialysis (HD) patients have not been thoroughly assessed. Methods: This study covers the epidemic period from May to June 2020 at the Hemodialysis (HD) Center in Rawalpindi. An observational Nested Case-Control study was devised to investigate the differences in outcomes and complications between hemodialysis patients testing positive and negative for the coronavirus. The study included a total of 294 registered hemodialysis patients, with a case group of 29 individuals testing positive for coronavirus compared to 29 COVID-negative counterparts from the same cohort. Various data, encompassing epidemiological, clinical, laboratory, and radiological characteristics, were systematically collected and analyzed. Results: Of the 294 hemodialysis patients, 29 (9.86%) were diagnosed with COVID-19 during the outbreak from May to June 2020. Notably, only two deaths were recorded among COVID-19-positive HD patients, and none were associated with pneumonia or lung failure. Additionally, only three patients with a positive COVID test were admitted to the Intensive Care Unit (ICU) for severe conditions (10.3%). Most COVID-19-diagnosed patients presented with mild-moderate respiratory symptoms. Conclusions: This study highlights the susceptibility of HD patients during the COVID-19 epidemic and underscores HD centers as high-risk areas. Patients with COVID-19 and undergoing hemodialysis typically exhibit mild clinical symptoms and are less likely to progress to severe pneumonia, attributed to compromised cellular immune function and an inability to mount cytokine storms. Key Words: Coronavirus, Hemodialysis, Patients